Seasonal clutch size decline and individual variation in the timing of breeding are related to female body condition in a non-migratory species, the Upland Goose Chloephaga picta leucoptera - Gladbach, Anja; Gladbach, David Joachim; Quillfeldt, Petra; Justus Liebig University Giessen (My University, 2010)
Several studies have shown that waterfowl females in good condition lay larger clutches and start egg-laying earlier in a breeding season. However, most of these studies lack corresponding data on individual condition and timing of breeding in different years. We analysed data on clutch size, egg size, hatching date and female body condition of a non-migratory species, the Upland Goose Chloephaga picta leucoptera, recorded in three seasons on New Island, Falkand Islands. We found a strong seasonal decline in both egg and clutch size. Egg size increased with clutch size. The mean egg volume and total clutch volume increased with female body condition and hatching date was earlier for females in higher body condition. Chicks hatched from nests with higher mean egg volume had higher early body condition. We also compared individual females between different study years and found that individual body condition showed a significant repeatability between years, whereas hatching date did not. While female aging did not systematically affect hatching date, females produced clutches that hatched earlier in years of higher body condition. We could thus show for the first time that the frequently reported negative relationship between female condition and hatching date also holds true on an individual basis. To our knowledge, this is the first study on seasonal clutch size decline in sheldgeese and one of a few in waterfowl comparing condition and timing of breeding within individuals between different years.
Keywords: Clutch size decline; Egg size; Chloephaga picta leucoptera; Reproductive investment; Body condition; ddc:570; ddc:590